Kekerasan Verebal pada Nama Julukan Bahasa Sasak Masyarakat Bebuak, Kopang, Lombok Tengah - Lalu Taufan Halas; Burhanuddin Burhanuddin; Saharudin Saharudin (Universitas Muhammadiyah Mataram, 2023)
This research took place in the Bebuak village, Kopang district, Central Lombok regency. The purpose of this study is to describe the lexicon of verbal violence in Sasak language nicknames in Bebuak village in everyday communication. The theoretical approach used is the anthropolinguistic approach. While, the methodological approach to research uses qualitative descriptive methods. For data collection using observation, record and interview. There are two results which can be drawn from this research. The first result is verbal abuse on nicknames in the Sasak language of the Bebuak people is calssified into two form, words and phrases. The second result is classification of the nickname function which consists of three function; the function of jokes/familiarity, the function of ridicule/insulting and the function as a differentiating identity. There are three sociocultural implications for Sasak society, namely the impact related to language ethics, which if the regulation is violated will get customary sanctions in the form of apologizing (mengaksama), fines (dedaosan) and not being spoken to for acertain time (kasepekang). Second, it is related to the norms inherent in the Bebuak community, namely the fading of the culture of manners in language and third, it relates to the psychis of the victim of verbal abse nicknames, where the victim will feel inferior, uncomfortable and embarrassed when the nickname is used in public places.